Einleitung: Asianismen seit dem 19. Jahrhundert.: „Asien“ als Gegenstand nationaler und transnationaler Diskurse und Praktiken - Frey, Marc; Spakowski, Nicola (Comparativ, 2008)
Over the last two decades, “Asia” has gained an important place in Western public discourse. Ideas of “Asia” as an entity, however, have a long tradition in Western discourse and were subject to significant changes over time. Within the region, concepts of a shared Asian identity and projects of integration and collaboration can be traced back to the late nineteenth century when Japan proposed to lead Asia in its struggle against Western colonialism and imperialism. Due to its own bid for power in the region, Japanese Pan-Asianism was not uncontested. Throughout the twentieth century, various actors at different levels of society developed a variety of definitions of “Asia” and alternative projects of intraregional collaboration. The term “Asianisms” is used to refer to both discursive constructs of Asia as a region as well as to political, economic, social and cultural practices related to them. The article gives an overview of the evolution of Asianisms since the late nineteenth century and introduces the individual contributions to this volume.